Future-proof accounting : data and technology strategies - Akpan, Mfon (Emerald Publishing Limited, 2024)
In today's rapidly evolving accounting landscape, success hinges on embracing cutting-edge technologies. Data analytics and blockchain technology have become indispensable tools for accountants as businesses increasingly digitize their operations. To remain at the forefront of the profession, accountants must possess the ability to decipher complex data and uncover emerging trends. Moreover, understanding the inner workings of blockchain technology is paramount for providing sound advice to clients. By continuously staying abreast of these groundbreaking technologies, accountants can secure their position as highly sought-after professionals. Future-Proof Accounting: Data and Technology Strategies equips accounting students, professors, and industry experts with the knowledge needed to navigate the dynamic realm of accounting. This essential resource provides readers with a comprehensive understanding of the latest technologies and their practical applications. Whether you seek to enhance your skills for the classroom or the workplace, this indispensable guide offers the tools necessary for triumph. Future-Proof Accounting: Data and Technology Strategies bridges the gap between theoretical knowledge and practical expertise, delving into the latest technological advancements and empowering students to cultivate proficiency in technologies that will shape their future careers.
Includes index.
Keywords: Accounting -- Technological innovations.; Business & Economics -- Accounting -- General.; Management accounting, bookkeeping and auditing.; Accounting.; elektronické knihy; electronic books